2021
DOI: 10.1161/jaha.120.019849
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Pulmonary Artery Pressure and Left Ventricle Stroke Volume Assessment Predicts Adverse Events in Patients With Pulmonary Embolism

Abstract: Background Certain echocardiographic parameters may serve as early predictors of adverse events in patients with hemodynamically compromising pulmonary embolism (PE). Methods and Results An observational analysis was conducted for patients with acute pulmonary embolism evaluated by a Pulmonary Embolism Response Team (PERT) between 2014 and 2020. The performance of clinical prediction algorithms including the Pulmonary Embolism Severity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Continuous measures of RVD seem to provide a more clinically relevant spectrum of risk, although these should be considered hypothesis-generating given the relatively few studies and limited number of continuous markers of RVD. There are numerous other promising markers of RVD that leverage the pathophysiology of reduced cardiac output [18][19][20] and RV-pulmonary artery decoupling [21][22][23][24], which did not have enough studies with similar outcomes for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous measures of RVD seem to provide a more clinically relevant spectrum of risk, although these should be considered hypothesis-generating given the relatively few studies and limited number of continuous markers of RVD. There are numerous other promising markers of RVD that leverage the pathophysiology of reduced cardiac output [18][19][20] and RV-pulmonary artery decoupling [21][22][23][24], which did not have enough studies with similar outcomes for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to increase the positive predictive value of TTE-derived RVD are needed to identify patients at higher risk of PE-related events. It is possible that new RVD parameters such as VTI or RV-pulmonary artery decoupling [18][19][20][21][22][23][24] using higher thresholds to define RVD or continuous measures of RVD that provide a spectrum of risk in combination with multimodality approaches that incorporate imaging, biomarkers and clinical data may enhance PE risk stratification in the future [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…who reported that only 270/326 (83%) patients had complete data [9,10]. Lastly, because performing a TTE was at the discretion of the attending physician, there have been some selection bias in this cohort (only 820/2067 patients had a TTE within 48 hours of diagnosis).…”
Section: Discussionmentioning
confidence: 95%
“…Current international guidelines on the diagnosis and management of PE recommend consideration of transthoracic echocardiography (TTE) for risk strati cation although there are no standardized echocardiographic measures to de ne the presence or absence of RVD [6]. The prognostic importance of TTE-derived RV-PA coupling indices such as tricuspid annular plane systolic excursion (TAPSE)/pulmonary artery systolic pressure (PASP) and stroke volume/PASP have been recently reported [7][8][9][10]. However, questions regarding the role of RV-PA coupling in PE still exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation